2018
DOI: 10.1590/1679-78254977
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of hermetic single-cell structure interfering with shaped charge jet

Abstract: On the basis of visual origin, shock wave reflection, and jet interference theories, this study aims to (1) divide the process of jet penetration into a hermetic single-cell structure into six parts, (2) establish a theoretical model of a single-cell structure interacting with a jet during its penetration into a structure, and (3) obtain the time expressions of a hermetic single-cell structure interfering with a jet. A residual penetration experiment is conducted to verify the accuracy of the model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The schematic of the interaction between the SCJ and LFCS is shown in Figure 3. The basic principle [16,17] between the LFCS and the SCJ is presented as follows:…”
Section: Physics Phenomena and Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The schematic of the interaction between the SCJ and LFCS is shown in Figure 3. The basic principle [16,17] between the LFCS and the SCJ is presented as follows:…”
Section: Physics Phenomena and Principlesmentioning
confidence: 99%
“…The researchers observed that the contour of bubbles formed no smooth curve, but that wave packets and jet particles only arrived at the penetration bottom when the foregoing particles were consumed completely during penetration. Huang et al [16,17] established a mechanical model of a diesel oil-filled hermetic structure that interferes with a jet and obtained the expressions of the interfered velocity range. They also verified the theoretical model via X-ray experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al considered the multiple impacts of the jet on the liquid and proposed that the liquid backflow caused by bottom reflection and cavity wall reflection interfered with the middle and rear segments of the shaped charge jet, respectively. They utilized the lateral velocity method to calculate the residual penetration depth of the jet after being disturbed by the liquid composite armor (Guo et al 2018. Zu et al analyzed the lateral migration of the disturbed jet and the lateral velocity generated by the breakup of the jet at a high standoff distance.…”
Section: Introductionmentioning
confidence: 99%